2014
DOI: 10.1177/107327481402100109
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Outcomes of Chemotherapy and Radiation in Morbidly Obese Patients with Locally Advanced Lung and Esophageal Cancers: A Single-Institution Experience

Abstract: the authors also clarify that the consequences of actual weight-based dosing of chemotherapy in the morbidly obese have not been adequately studied and hence remain unknown. Second, this guideline provides little advice on how to determine chemotherapy dosage in obese patients who are receiving concomitant chemotherapy and radiation, particularly to the thorax. With concomitant therapy, it is tenable that surrounding vital structures can sustain notable damage as a result of higher chemotherapy doses that mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…For example, one study demonstrated a 5.5-fold increased risk for dose-limiting chemotoxicity among patients with sarcopenic obesity, with no increased risk among normal-weight patients with sarcopenia (145). Increased risk of dose-limiting toxicity may be due to reduced volume of distribution in lean body mass relative to calculated body surface area, with significant variation in the effective volume of distribution in obesity (145,146). In addition, patients with obesity often exhibit a greater number of baseline comorbidities, which may impact treatment tolerance (147,148).…”
Section: Impact Of Obesity On Cancer Treatment Outcomes Chemotherapymentioning
confidence: 99%
“…For example, one study demonstrated a 5.5-fold increased risk for dose-limiting chemotoxicity among patients with sarcopenic obesity, with no increased risk among normal-weight patients with sarcopenia (145). Increased risk of dose-limiting toxicity may be due to reduced volume of distribution in lean body mass relative to calculated body surface area, with significant variation in the effective volume of distribution in obesity (145,146). In addition, patients with obesity often exhibit a greater number of baseline comorbidities, which may impact treatment tolerance (147,148).…”
Section: Impact Of Obesity On Cancer Treatment Outcomes Chemotherapymentioning
confidence: 99%